Couple-level determinants of syphilis infection among heterosexual married couples of reproductive age in Guangdong Province, China: A population-based cross-sectional study - Han, Lu; Xiong, Wenxue; Li, Mingzhen; Li, Rui; Wu, Jiabao; Tang, Xijia; Ling, Li; Liu, Xiaohua (Frontiers in Public Health, 2022)
Syphilis remains a major public health problem worldwide, and its prevention requires knowledge of factors that go beyond the individual-level. However, most syphilis-related studies have focused on individual-level and regional-level factors, neglecting couple-level factors. Thus, this study aimed to explore couple-level determinants of syphilis infection among heterosexual married couples. This population-based cross-sectional study used data from heterosexual married couples who participated in the National Free Preconception Health Examination Project in Guangdong Province, China during 2014-2019. The syphilis infection was tested by the rapid plasma reagin test. Couple-level data were obtained by combining information provided by the man and woman living in the same household. Multivariate logistic models were employed to explore the couple-level determinants of syphilis infection by gender after adjusting for potential confounders. A total of 1,755,156 couples were recruited in this analysis. The seroprevalence was 0.25% (95%CI: 0.24%-0.25%) and 0.26% (95%CI: 0.25%-0.27%) among men and women, respectively. The median age was 28.0 (interquartile range, IQR: 25.0-31.0) years, and the median duration of marriage was 0.2 (IQR: 0.0-2.5) years. After adjusting for individual and regional-level variables, duration of marriage was a protective factor for syphilis infection in men (adjusted odds ratios, AOR: 0.97; 95% CI: 0.96-0.98) and women (AOR: 0.95, 95% CI: 0.94-0.96). The age gap and the difference in education level between the husband and wife were associated with syphilis infection, but these associations were somewhat different between men and women. Condom use was negatively associated with syphilis infection in men (AOR: 0.77; 95% CI: 0.70-0.84) and women (AOR: 0.77, 95% CI: 0.71-0.84). Our results also showed that couple mobility and the number of children were not statistically significant determinants of syphilis infection among heterosexual married couples. This study contributes to a more comprehensive understanding of syphilis outcomes in individuals in the context of marriage in China. Several couple-level factors are indeed associated with syphilis infection, but these associations differ between men and women. Couple-based strategies that engage both women and men and efforts to promote condom use among heterosexual married couples need to be developed and further evaluated for syphilis prevention.